Cytokine, activation marker, and chemokine receptor expression by individual CD4(+) memory T cells in rheumatoid arthritis synovium - Nanki, Toshihiro (BioMed Central, 2000)
INTRODUCTION: In RA large numbers of CD4(+) memory T cells infiltrate the inflamed synovium [1,2,3]. The accumulated CD4(+) memory T cells in the RA synovium appear to be activated, because they express cytokines and activation markers [4,5,6,7,8]. Expressed cytokines and activation markers should play important roles in the pathogenesis of RA. However, the frequency of cytokine expression by RA synovial CD4(+) T cells has not been analyzed accurately. Recently, the roles of chemokine and chemokine receptor interactions in T-cell migration have been intensively examined. Interactions of chemokine and chemokine receptors might therefore be important in the accumulation of the CD4(+) T cells in the RA synovium. Accordingly, correlation of cytokine and chemokine receptor expression might be important in delineating the function and potential means of accumulation of individual CD4(+) memory T cells in the RA synovium. In the present study we analyzed cytokine (IL-2, IL-4, IL-6, IL-10, IL-13, IFN-γ , TNF-α , and LT-α ), activation marker (CD154 [CD40 ligand] and TRANCE - also called receptor activator of nuclear factor κ B ligand [RANKL] or osteoclast differentiation factor [ODF]), and chemokine receptor expression by individual CD4(+) memory T cells isolated from rheumatoid synovium and blood. To achieve this we employed a single-cell reverse transcription (RT) polymerase chain reaction (PCR) technique. This technique made it possible to correlate mRNAs expressed by individual CD4(+) memory T cells in the synovium and blood. MATERIALS AND METHOD: Synovial tissues from three RA patients and peripheral blood mononuclear cells from two RA patients and a normal donor were analyzed. Cytokine (IL-2, IL-4, IL-6, IL-10, IL-13, IFN-γ, TNF-α, and LT-α ) and activation marker (CD154 and TRANCE) expression by individual CD4(+)CD45RO(+) T cells from RA synovium or blood were analyzed using a single-cell RT-PCR. In brief, single CD4(+)CD45RO(+)T cells was sorted into each well of a 96-well PCR plate using a flow cytometer. cDNA from individual cells was prepared, and then the cDNA was nonspecifically amplified. The product was then amplified by PCR using gene-specific primers to analyze cytokine and activation marker expression. RESULTS: Cytokine and activation marker expression by individual CD4(+)CD45RO(+)T cells from RA synovial tissues was analyzed using a single-cell RT-PCR method. Expression of mRNAs was analyzed in 152 individual synovial tissue CD4(+)CD45RO(+) T cells sorted from three RA patients in which T-cell receptor (TCR) Cβ mRNA was detected. Frequencies of CD4(+) memory T cells expressing cytokine and activation marker mRNA in RA synovium are shown in Table 1. IL-2, IL-4, and IL-6 were not expressed by the synovial tissue CD4(+)CD45RO(+) T cells, whereas 2-20% of cells expressed the other cytokine mRNAs. Few correlations between cytokine and activation marker mRNAs were observed. Notably, no cells contained both IFN-γ and LT-α mRNAs, cytokines that are thought to define the T-helper (Th)1 phenotype [9]. However, the frequency of TRANCE-positive cells in IL-10-positive cells was significantly higher than that in IL-10-negative cells (Table 2). Moreover, the frequency of TRANCE-positive cells in TNF-α-positive cells was also significantly higher than that in TNF-α-negative cells. Varying percentages of CD4(+) memory T cells expressed CC and CXC chemokine receptors. The frequency of CCR5-positive cells in IFN-γ-positive cells was significantly higher than that in IFN-γ-negative cells, whereas the frequency of CCR6-positive cells in LT-α-positive cells was significantly higher than that in LT-α-negative cells, and the frequency of CCR7-positive cells in IL-10-positive cells was significantly higher than that in IL-10-negative cells. Furthermore, the frequency of CXCR4-positive cells in TRANCE-positive cells was significantly higher than that in TRANCE-negative cells. Expression of cytokine and activation marker mRNAs was also analyzed in 48 individual peripheral blood CD4(+)CD45RO(+) T cells from two RA patients. IL-2, IL-4, IL-6, and LT-α were not expressed by the peripheral CD4(+)CD45RO(+) T cells, whereas 4-17% of cells expressed the other markers. The most striking difference between synovial tissue and peripheral blood CD4(+) memory T cells was the presence of LT-α expression in the former, but not in the latter. IFN-γ and TNF-α were not expressed by normal peripheral blood CD4(+) memory T cells, although they were expressed by RA peripheral blood CD4(+) memory T cells. DISCUSSION: The present study employed a single-cell PCR technology to analyze cytokine expression by unstimulated RA synovial tissue CD4(+) memory T cells immediately after isolation, without in vitro manipulation. The results confirm the Th1 nature of rheumatoid inflammation. It is noteworthy that no individual synovial CD4(+) memory T cells expressed both IFN-γ and LT-α mRNAs, even though these are the prototypic Th1 cytokines [9]. These results imply that, in the synovium, regulation of IFN-γ and LT-α must vary in individual cells, even though both Th1 cytokines can be produced. The present data showed that CCR5 expression correlated with IFN-γ but not with LT-α expression by synovial CD4(+) memory T cells. It has been reported that CCR5 expression is upregulated in RA synovial fluid and synovial tissue T cells [10,11,12] and that CCR5 Δ 32 deletion may have an influence on clinical manifestations of RA [13], suggesting that CCR5 might play an important role in RA. Recently, it has been claimed that CCR5 was preferentially expressed by Th1 cell lines [14,15]. However, in the present study CCR5 was not expressed by all IFN-γ-expressing cells. Moreover, CCR5 expression did not correlate with expression of LT-α by RA synovial CD4(+) memory T cells. Therefore, it is unclear whether CCR5 is a marker of Th1 cells in RA synovium. IL-10 expression correlated with CCR7 expression by RA synovial CD4(+) memory T cells. Recently, it was reported [16] that in the blood CCR7(+)CD4(+) memory T cells express lymph-node homing receptors and lack immediate effector function, but efficiently stimulate dendritic cells. These cells may play a unique role in the synovium as opposed to in the blood. By producing IL-10, they might have an immunoregulatory function. In addition, IL-10 expression also correlated with expression of TRANCE. Although it is possible that IL-10 produced by these cells inhibited T-cell activation in the synovium, TRANCE expressed by these same cells might function to activate dendritic cells and indirectly stimulate T cells, mediating inflammation in the synovium. These results imply that individual T cells in the synovium might have different, and sometimes opposite functional activities. LT-α expression correlated with CCR6 expression by synovial CD4(+) memory T cells. It has been reported that CCR6 is expressed by resting peripheral memory T cells [17], whereas LT-α expression is associated with the presence of lymphocytic aggregates in synovial tissue [7]. The correlation between the expression of these two markers therefore suggests the possibility that CCR6 may play a role in the development of aggregates of CD4(+) T cells that are characteristically found in rheumatoid synovium. TRANCE is known to be expressed by activated T cells, and can stimulate dendritic cells and osteoclasts [18]. Of note, TRANCE-mediated activation of osteoclasts has recently been shown [19] to play an important role in the damage to bone that is found in experimental models of inflammatory arthritis. It is therefore of interest that TRANCE was expressed by 3-16% of the RA synovial CD4(+) memory T cells. Of note, 67% of TNF-α-positive cells expressed TRANCE. In concert, TNF-α and TRANCE expressed by this subset of CD4(+) memory T cells might make them particularly important in mediating the bony erosions that are characteristic of RA. Interestingly, there was a correlation between expression of IFN-γ and IL-10 in RA peripheral blood CD4(+) memory T cells. In RA peripheral blood, CD154 expression correlated with that of CXCR3 by CD4(+) memory T cells. It has been claimed [15] that CXCR3 is preferentially expressed by in vitro generated Th1 cells. However, in the present study CXCR3 did not correlate with IFN-γ expression. Although IFN-γ and TNF-α mRNAs were expressed in vivo by peripheral blood CD4(+) T cells from RA patients, LT-α mRNA was not detected, whereas IFN-γ , TNF-α , and LT-α were not detected in samples from healthy donors. These findings indicate that RA peripheral blood CD4(+) memory T cells are stimulated in vivo, although they do not express LT-α mRNA. The present studies indicate that the frequencies of CD4(+) memory T cells that expressed IFN-γ in the blood and in the synovium are comparable. These results imply that activated CD4(+) memory T cells migrate between blood and synovium, although the direction of the trafficking is unknown. The presence of LT-α mRNA in synovium, but not in blood, indicates that CD4(+) memory cells are further activated in the synovium, and that these activated CD4(+) memory T cells are retained in the synovium until LT-α mRNA decreases. In conclusion, CD4(+) memory T cells are biased toward Th1 cells in RA synovium and peripheral blood. In the synovium, IFN-γ and LT-α were produced by individual cells, whereas in the rheumatoid blood no LT-α-producing cells were detected. Furthermore, there were modest correlations between individual cells that expressed particular cytokines, such as IL-10, and certain chemokine receptor mRNAs.